PELAKSANAAN PUTUSAN ARBITRASE ASING PADA PERKARA PENANAMAN MODAL ASING DI INDONESIA (STUDI KASUS PERTAMINA VS. KARAHA BODAS COMPANY) - Yohana, Rachel (TANJUNGPURA LAW JOURNAL, 2019)
Arbitration by its advantages is often chosen by businessmen to resolve cases, however at the same time there are some weaknesses that actually do not make it as an efficient choice in resolving cases. Especially when the opposite parties are not cooperative and not upholding the spirit of arbitration. The refusal and annulment of foreign arbitral awards, for instance, has made a settlement process seems has no end and no legal certainty to enforcet its awards. In the case of PERTAMINA VS. Karaha Bodas Company, PERTAMINA made a claim of annulment of the arbitration award in Geneva, Switzerland on December 18th, 2000 at The Central Jakarta District Court. This claim was then accepted and the panel of judges decided to annul the a-quo arbitration award, its legal proceedings continued until the process by The Indonesias Supreme Court. A wrong court award in responding to foreign arbitration awards may affect the consideration of foreign investment in a country, a bad precedent can damage the consideration of foreign investment. The findings of this study indicate PERTAMINA is not cooperative and does not support legal certainty for the implementation of foreign arbitral awards. Whereas the Awards of the Panel of Judges of the Central Jakarta District Court set a bad precedent and gave a negative impression on the consideration of arbitration and foreign investment in Indonesia. The Supreme Court Judge Panel in its award stated that it was not authorized by the Central Jakarta District Court to annul the a quo arbitration award is being a good precedent, indicating legal certainty in the implementation of foreign arbitration decisions and foreign investment in Indonesia.Arbitrase dengan berbagai kelebihannya kerap dipilih pelaku bisnis untuk menyelesaikan perkara yang timbul, namun bersamaan dengan itu beberapa kelemahan yang ada justru tidak menjadikannya sebagai pilihan yang efisien dalam menyelesaikan perkara. Terlebih ketika berhadapan dengan pihak yang tidak kooperatif, serta tidak menjunjung semangat berarbitrase. Upaya penolakan dan pembatalan putusan misalnya, menjadikan proses perkara seolah tidak ada habis-habisnya dan tidak ada kepastian hukum untuk melaksanakan putusan. Dalam perkara PERTAMINA VS. Karaha Bodas Company, PERTAMINA melakukan gugatan pembatalan putusan arbitrase Jenewa, Swiss tanggal 18 Desember 2000 ke Pengadilan Negeri Jakarta Pusat, gugatan ini kemudian diterima dan majelis hakim memutuskan batal putusan arbitrase a quo, upaya hukum berlanjut hingga proses peninjauan kembali. Putusan pengadilan yang keliru dalam menanggapi putusan arbitrase asing dapat berpengaruh pada pertimbangan penanaman modal asing di suatu negara, preseden buruk menjadikan negara seolah tidak ramah pada putusan arbitrase asing. Temuan dari penelitian ini menunjukkan PERTAMINA tidak kooperatif dan tidak mendukung kepastian hukum bagi pelaksanaan putusan arbitrase asing. Sedangkan Putusan Majelis Hakim Pengadilan Negeri Jakarta Pusat menjadi preseden yang buruk dan menimbulkan kesan negatif terhadap pandangan berarbitrase dan penanaman modal asing di Indonesia. Majelis Hakim Mahkamah Agung dalam putusan peninjauan kembali yang tetap pada sikapnya menyatakan tidak berwenang Pengadilan Negeri Jakarta Pusat membatalkan putusan arbitrase a quo menjadi preseden yang baik, menunjukkan adanya kepastian hukum dalam pelaksanaan putusan arbitrase asing dan penanaman modal asing di Indonesia.